KEKUATAN KEPEDULIAN: DARI TINDAKAN ALTRUISTIK MENUJU PSYCHOLOGICAL WELL-BEING PADA RELAWAN DEWASA AWAL - Audrey Felicia Lie; Rahmah Hastuti (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2025)
This study aimed to examine the relationship between altruism and psychological well-being (PWB) among early adult volunteers. Altruism refers to the tendency to help others voluntarily, while PWB includes six core dimensions: self-acceptance, positive relations, autonomy, environmental mastery, purpose in life, and personal growth. A total of 138 volunteers aged 20–40 years from Community X were selected using purposive sampling. Data were collected using the Self-Report Altruism Scale and the Indonesian-adapted version of the Ryff Psychological Well-Being Scale. Spearman's rho correlation was used due to non-normal data distribution. The results showed that most participants had moderate to high levels of altruism and PWB. However, altruism was not significantly associated with overall PWB (r = 0.041; p = 0.635), except for the autonomy dimension, which showed a significant positive correlation (r = 0.192; p = 0.024). These findings suggest that altruistic behavior does not necessarily enhance general psychological well-being but does contribute to a sense of independence in decision-making. This study expands the understanding of the dynamics between volunteering and well-being within a collectivist cultural context. Future research is recommended to explore potential mediators such as empathy and prosocial motivation, as well as to broaden the scope and sectors of volunteer activities. ABSTRAK Penelitian ini bertujuan untuk mengkaji hubungan antara altruisme dan psychological well-being (PWB) pada volunteer dewasa awal. Altruisme adalah kecenderungan membantu secara sukarela, sedangkan PWB mencakup enam aspek utama: penerimaan diri, relasi positif, autonomy, penguasaan lingkungan, tujuan hidup, dan pertumbuhan pribadi. Sebanyak 138 volunteer berusia 20–40 tahun dari Komunitas X dipilih menggunakan purposive sampling. Data dikumpulkan melalui Self-Report Altruism Scale dan Ryff Psychological Well-Being Scale versi Indonesia. Analisis Spearman's rho digunakan karena data tidak berdistribusi normal. Hasil menunjukkan sebagian besar partisipan memiliki tingkat altruisme dan PWB sedang hingga tinggi. Namun, altruisme tidak berhubungan signifikan dengan PWB secara keseluruhan (r = 0,041; p = 0,635), kecuali pada dimensi autonomy yang menunjukkan hubungan positif signifikan (r = 0,192; p = 0,024). Temuan ini mengindikasikan bahwa perilaku altruistik tidak serta merta meningkatkan kesejahteraan psikologis secara umum, tetapi berkontribusi pada aspek kemandirian dalam pengambilan keputusan. Studi ini memperluas pemahaman mengenai dinamika volunteering dan kesejahteraan dalam konteks budaya kolektivis. Penelitian lanjutan disarankan untuk mengeksplorasi peran mediator seperti empati, motivasi prososial, serta memperluas konteks dan sektor kegiatan kerelawanan.